Coaching of Insolvent Entrepreneurs and the Change in Coping Resources, Health, and Cognitive Performance. Issue 2 (27th February 2020) - Schermuly, Carsten C.; Wach, Dominika; Kirschbaum, Clemens; Wegge, Jürgen
Abstract : As coaching becomes an established learning and development tool, it expands to new work contexts and relevant populations. Exploring coaching outcomes in insolvent entrepreneurs is a new and promising field. Business failure is a devastating experience for entrepreneurs, associated with negative emotions and adverse psychological and physiological reactions. Our study is the first to examine if coaching can help improve the coping resources, health, and cognitive performance of insolvent entrepreneurs. The results of our pre‐post‐test‐within‐subject analyses based on 19 participants show a positive improvement in psychological well‐being, vital exhaustion, and vigilance. By contrast, no improvements were found with regard to coping resources and biomarkers such as stress hormones concentrations in hair. Unexpectedly, the working alliance between client and coach did not increase the improvements following coaching. Our findings contribute to the growing literature on the effects of coaching; however, our results should be interpreted cautiously as unfortunately we had no opportunity to include a control group in our research design.